Hispanic Methodists, Presbyterians, and Baptists in Texas - Barton, Paul, 1961- (Jack and Doris Smothers series in Texas history, life, and culture, 2006)
The Tejano/a Catholic worldview -- "Onward Christian soldiers": Anglo-Protestant missionaries -- "Jesus is all the world to me": los protestantes' appropriation of Anglo-American Protestantism -- "Jesús es mi Rey Soberano": the Mexican-American character of los protestantes -- "Somos uno en el espíritu"? the relationship between los protestantes and Catholicism.